MODERASI GAYA KEPEMIMPINAN ATAS PENGARUH PARTISIPASI ANGGARAN TERHADAP BUDGETARY SLACK - Aristanti Widyaningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
The research explains the influence of budget participation toward budgetary slack both directly and non directly with serves as moderating variables by leadership style. The purpose of this research is to examine about (a) direct influence and significant between budget participation and budgetary slack, (b) leadership style can moderate that influence between budget participation and budgetary slack.The research samples are head of special distric in Bandung City Government with 165 population of special distric. The sampling is done by purposive sampling and proportional sampling. The sample is 62 in this research. Data collecting is done by direct distribution with uses the question before, so the validity and reability had been fullfilled. From 120 questioner, there are 62 questioner is gotten and fullfilled completely (51,67%). After colecting the data, through validity and realibility test that have fullfilled classic asumption then it is analyzed by simple regretion for testing the first hyphotesis and regretion with absolute difference score for testing the second and the third hypothesis.The result of the research shows: first, there is direct influence R square 15,7% and the significant is 0,001 between budget participation and budgetary slack. Secondly, the absolute difference score between budget participation and leadership style produce R square 17,5% and it doesn’t evidence to moderate the influence between budget participation and budgetary slack partially.